Peningkatan Hasil Belajar Sejarah Kebudayaan Islam Menggunakan Model Discovery Learning - Ari Susetiyo (EduBase : Journal of Basic Education, 2022)
This study was conducted with the aim to determine the use of discovery learning model in order to improve the learning outcomes of students of Islamic cultural history subjects in madrasah ibtida’iyah miftahul huda in chapter islam enters Indonesia. Imrove the learning outcomes of class VI students in madrasah ibtida’iyah miftahul huda. This study ia a class action research (PTK) consists of the first stage of planning, action, observation, and reflection. In the process of collecting data including, observation, tests and documentation. Data were processed using quantitative data analysis. The result of this study indicate that the learning model of discovery learning can improve the learning outcomes of students of Islamic cultural history subjects in madrasah ibtida’iyah miftahul huda. In the first stages of the first meeting of students (37,93%) who have achieved KKM, while the other 15 students or in percentage (62,06%) has not been achieved, in the first cycle of the second meeting showed that completed as many as 12 students (58,62%) and unfinished as many as 11 students (41,37%) students, in the second cycle of the first meeting of the students obtained completeness (75,86%) as many as 17 students from 23 students graduated in achieving KKM standarts, 6 students (24,13%) who have not reached the standards of KKM, the second cycle of the second meeting proved there is an increase in students who achieve KKM, of the total 23 students in class VI who have reached KKM as many as 21 students (93,10%) and who have not reached KKM there are 2 students (6,89%) increased. Learning outcomes of Islamic cultural history based on these results it can be concluded that by using the discovery learning model can improve student learning outcomes in the subject of Islamic cultural history. Abstrak Penelitian ini dilakukan dengan tujuan untuk mengetahui penggunaan model Discovery Learning agar dapat meningkatkan hasil bepembelajaran siswa mata pelajaran Sejarah Kebudayaan Islam di Madrasah Ibtida’iyah Miftahul Huda pada bab Islam masuk di Indonesia. Dapat meningkatkan hasil belajar siswa kelas VI di Madrasah Ibtida’iyah Miftahul Huda. Penelitian ini merupakan penelitian tindakan kelas (PTK) terdiri dari tahapan pertama yaitu perencanaan, tindakan, pengamatan, dan juga refleksi.Pada proses pengumpulan data diantaranya, observasi, tes dan dokumentasi. Data diolah dengan menggunakan analisis data kuantitatif. Hasil dari penelitian ini menunjukkan bahwasanya model pembelajaran discovery learning dapat meningkatkan hasil belajar siswa mata pelaajran sejarah kebudayaan islam di Madrasah Ibtida’iyah Miftahul Huda. Pada tahapan siklus I pertemuan pertama 8 siswa (37,93%) yang telah mencapai KKM, sedangkan 15 siswa lainnya atau dalam presentase (62,06%) belum tercapai, pada siklus I pertemuan kedua menunjukkan yang tuntas sebanyak 12 siswa (58,62%) dan yang belum tuntas sebanyak 11 siswa (41,37%) siswa, Pada siklus II pertemuan pertama ketuntasan siswa didapat (75,86%) sebbanyak 17 siswa dari 23 siswa lulus dalam mencapai standar KKM, 6 siswa (24,13%) yang belum mencapau standar KKM, ssiklus II pertemuan kedua terbukti ada peningkatan siswa yang mencapai KKM, dari keseluruhan 23 siswa dikelas VI ang telah mencapai KKM sebanyak 21 siswa (93,10%) dan yang belum mencapai KKM ada 2 siswa (6,89%), meningkat. Haisl belaajr SKI Berdasarkan hasil tersebut dapat disimpulkan bahwa dengan memakai model Discovery learning dapat meningkatkan hasil belaajar siswa pada mata pelajaran sejarah kebudayaan islam.